Nanoimprinted SERS Sensors for Chemical and Biological Detection. (16th January 2017) - Strack, Guinevere; Fitzgerald, Michaela; Su, Junwei; Pelletier, Margery G. H.; Gaines, Peter; Sun, Hongwei; Kurup, Pradeep; Mosurkal, Ravi
ABSTRACT: Herein, we demonstrate a facile, rapid, and scalable method to fabricate polymer-based gratings for surface-enhanced Raman spectroscopy (SERS) sensors. To accomplish this, epoxy nanostripe arrays on silicon substrates were prepared using thermal annealing and UV-cross-linking. After preparation of the nanostripe arrays, the surface was briefly treated with oxygen plasma, which decreased the surface energy and enabled the growth of AgNPs on the polymer surface using a simple, low-cost, aqueous-based synthesis procedure. The SERS substrates exhibited a detection limit of ∼1 pM using rhodamine 6G (R6G). In addition, preliminary work with E. coli DH5 showed that the nanoimprinted substrates can be used to obtain Raman spectra of washed bacteria cells.